2007
DOI: 10.1016/j.dnarep.2007.01.013
|View full text |Cite
|
Sign up to set email alerts
|

p53 promotes the fidelity of DNA end-joining activity by, in part, enhancing the expression of heterogeneous nuclear ribonucleoprotein G

Abstract: Many studies have suggested the involvement of wild-type (wt) p53 in the repair of DNA double-strand breaks (DSBs) via DNA end-joining (EJ) process. To investigate this possibility, we compared the capacity and fidelity of DNA EJ in RKO cells containing wt p53 and RKO cells containing no p53 (RKO cells with p53 knockdown). The p53 knockdown cells showed lower fidelity of DNA EJ compared to the control RKO cells. The DNA end-protection assay revealed the association of a protein complex including heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Our previous study showed that the HEp-2 cells lack endogenous hnRNP G expression and are a proper cell line to test effect of exogenous hnRNP G on various biochemical processes [8,9]. Indeed, we demonstrated that wt hnRNP G elicited tumor suppressive activity, and its overexpression led to marked induction of Txnip mRNA in HEp-2 cells [8].…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Our previous study showed that the HEp-2 cells lack endogenous hnRNP G expression and are a proper cell line to test effect of exogenous hnRNP G on various biochemical processes [8,9]. Indeed, we demonstrated that wt hnRNP G elicited tumor suppressive activity, and its overexpression led to marked induction of Txnip mRNA in HEp-2 cells [8].…”
Section: Resultsmentioning
confidence: 80%
“…In fact, there is no report describing the presence of a DNA binding domain in hnRNP G protein. Apart from its function in RNA splicing, the other physiological roles of hnRNP G have yet to be fully understood and may include tumor suppression and DNA repair mechanisms [8,9]. Recent studies have shown that several hnRNP family proteins, such as D0B, E2BP, and K, are able to bind to the promoters of various cellular genes [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA-binding motif protein, X-linked (RBMX) is a heterogeneous nuclear ribonucleoprotein (Shin et al 2008a) and is made of 391 amino acid residues containing the RNA binding domain at the amino terminus of the protein (Shin et al 2007). This architectural feature exposits the physical association of RBMX with RNA, which may be required in RNA processing and metabolism (Shin et al 2006(Shin et al , 2007.…”
Section: Introductionmentioning
confidence: 98%